The Adjudicator's Toolkit and the Force of International Law : Comparing Trade and Investment Disputes - Strain, Nicola (International Law E-Books Online, Collection 2024., 2024)
Adjudicators have been placed at the forefront in the search for systemic order within the pluralist international legal order, acting as guardians of the international legal system. Yet, they do so under increasing pressure from the governments